2017
DOI: 10.1097/mlr.0000000000000632
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress, Multimorbidity, and Risk for Hospitalizations for Ambulatory Care–sensitive Conditions

Abstract: Elevated perceived stress levels are associated with increased risk for ACSC-related hospitalization and poor short-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…But, because these positive psychologic factors propagate across social groups, these findings may extend to the community level as well, and emerging evidence suggests that higher levels of neighbourhood social well-being are indeed associated with lower levels of perceived chronic stress among residents 52. This logic is further supported by findings from a large population-based cohort study that reported that groups with the highest quintile of perceived stress experienced an approximately 1.5-fold higher risk of hospitalisation for ambulatory sensitive conditions, after adjusting for demographics, predisposing conditions, multimorbidity and socioeconomic factors 64…”
Section: Discussionmentioning
confidence: 65%
“…But, because these positive psychologic factors propagate across social groups, these findings may extend to the community level as well, and emerging evidence suggests that higher levels of neighbourhood social well-being are indeed associated with lower levels of perceived chronic stress among residents 52. This logic is further supported by findings from a large population-based cohort study that reported that groups with the highest quintile of perceived stress experienced an approximately 1.5-fold higher risk of hospitalisation for ambulatory sensitive conditions, after adjusting for demographics, predisposing conditions, multimorbidity and socioeconomic factors 64…”
Section: Discussionmentioning
confidence: 65%
“…One in fifty may not sound as many, but this figure corresponds to almost one patient per week per GP and around 75,000 patients in Denmark during 6 months. Patients with stress often requires several consultations, including examinations of psychological and physical symptoms, talk therapy, introduction and adjustment of pharmaceutical treatment, sick notes and declarations to employer and municipality; psychological stress is associated with high use of both elective and acute services by the GP and in the hospitals [29, 30]. This reflects a substantial burden on society at large and on general practice in specific.…”
Section: Resultsmentioning
confidence: 99%
“…ICD‐9 or ICD‐10 diagnosis codes were extracted from both inpatient and outpatient data sources for the majority of the multimorbidity measures (18/22) 2,22–24,26–40,40,41,50–60 . Nine measures extracted supplementary information on diseases from pharmacy data sources, using mostly the Anatomical Therapeutic Chemical Classification System (ATC) code 2,23,27,31,33–39,54–60 . Other databases included death registries 23 and laboratory data 40,41 .…”
Section: Resultsmentioning
confidence: 99%
“…2,23,27,31,[33][34][35][36][37][38][39][54][55][56][57][58][59][60] Other T A B L E 1 Characteristics of multimorbidity measures relying on administrative data using the ICD coding system…”
mentioning
confidence: 99%